Crossing the Gap: Using Competency-Based Assessment to Determine Whether Learners Are Ready for the Undergraduate-to-Graduate Transition. (March 2019) - Murray, Katherine E.; Lane, J. Lindsey; Carraccio, Carol; Glasgow, Tiffany; Long, Michele; West, Daniel C.; O'Connor, Meghan; Hobday, Patricia; Schwartz, Alan; Englander, Robert
Abstract : In 2011, the Education in Pediatrics Across the Continuum (EPAC) Study Group recruited four medical schools (University of California, San Francisco; University of Colorado; University of Minnesota; and University of Utah) and their associated pediatrics clerkship and residency program directors to be part of a consortium to pilot a model designed to advance learners from undergraduate medical education (UME) to graduate medical education (GME) and then to fellowship or practice based on competence rather than time spent in training. The central design features of this pilot included predetermined expectations of performance and transition criteria to ensure readiness to progress from UME to GME, using the Core Entrustable Professional Activities for Entering Residency (Core EPAs) as a common assessment framework. Using this framework, each site team (which included, but was not limited to, the EPAC course, pediatric clerkship, and pediatric residency program directors) monitored learners' progress, with the site's clinical competency committee marking the point of readiness to transition from UME to GME (i.e., the attainment of supervision level 3a). Two of the sites implemented time-variable transition from UME to GME, based on when a learner met the performance expectations and transition criteria. In this Article, the authors describe each of the four sites' implementation of Core EPA assessment and their approach to gathering the data necessary to determine readiness for transition. They conclude by offering recommendations and lessons learned from the pilot's first seven years of development, adaptation, and implementation of assessment strategies across the sites, and discussing next steps.